Analisis Kandungan N, P, K, dan C-Organik pada Tanah Datar dan Tanah Miring di Kebun Silau Dunia Afdeling III PT Perkebunan Nusantara IV Regional I - Simanjuntak, Riki Rikardo; Manurung, Saroha; Djaingsastro, Aulia Juanda (Dinasti Research, 2026)
This research is motivated by the importance of soil fertility in supporting oil palm productivity through the availability of Nitrogen (N), Phosphorus (P), Potassium (K), and C-organic nutrients. The results showed that the total N content on sloping and flat land had an average of 0.13% and 0.12%, respectively, with a low category. The available P content had an average of 27.40 ppm on sloping land and 26.61 ppm on flat land with a high category. In general, the K content was classified as moderate and C-organic was classified as low in both land conditions. The t-test results showed no significant difference between flat and sloping land regarding the analyze dnutrient content. Soil functions as a medium for providing nutrients, but intensive management and continuous use of chemical fertilizers can reduce soil quality, especially organic matter. Therefore, analysis of N, P, K and C-organic is necessary to evaluate soil fertility and determine the appropriate fertilization strategy. The elements N, P, and K are essential macronutrients for plant growth, while organic C plays a role in improving the physical, chemical, and biological properties of the soil. The research was conducted at the Silau Dunia Plantation, Afdeling III, PT. Perkebunan Nusantara IV Regional I from February 2026 to May 2026, using a comparative quantitative method with laboratory analysis. Soil samples were taken purposively on flat and sloping land using the composite method (three replications). The parameters analyzed included total N, available P, K, and organic C, then tested using a t-test. The results showed that total N was low, available P was high, K was moderate, and organic C was low in both land conditions. There was no significant difference between flat and sloping land. Nutrient variations are thought to be more influenced by land management, fertilization, and environmental conditions.